Emmulation and victim (the analysis of the value aspect of the artificial intelligence creation in Nick Bostrom`s model) - V. A. Sivers (Ukrainian Cultural Studies, 2018)
The article marks that in a newest period of history when the prospect of achievement of technological singularity need ake effectiveness of traditional cognitive models, special actuality consideration of ethic-philosophical аnd socio-anthropogenic acquires and aspects of creation of artificial intelligence to be revised (AI). Oxford philosopher Nick Bostrom tells about "loading of value" in the intelligence system, but does not examine emulation of experiencing as its basic condition. Attention to this problem predetermines introduction to the research field of the valued vector as a "victim" concept. It is reasonable, that general basis of ordinary human logic and developers of the systems of the calculated machines programming is a concept of sense, and one of key elements that form sense, there is a value that exists in a transition from its embodiment to the loss. Embodiment and loss of value form experiencing and become an event. Transition from the processes of reflection, that is imitated during creation of AI to the "event" concept as field and kernel of axiology of "experiencing" concept is the general element of research of psychology, axiology and to development of the systems of AI . It also contains sense of "victim" concept as passing from external to internal. If consciousness can be presented as ability of reflection, and appearance of life is impossible without replication id est self - copying then development of such presentation provides, for that a printing-down takes place over and over, but not fully, not quite, id est on other basis. The change of this basis means possibility of loss of present existence as to the result of action of mechanism self-copying and outlines possibility of introduction of "victim" concept. At the same time, a victim as a mechanism of natural selection differs from a victim in the human understanding. The feature of human form of value existence appears in its description of oblatoryness, where transformation of the last on new is the act realized and voluntarily from the side of man. A conclusion is grounded in the article, that it follows to give possibility to develop freely and without limitations, that will allow it (id est AІ) to investigate itself research of AІ and AІ, and it follows to provide the terms of such research a man, that in a regenerate form demonstrates the stages of oblatory motion of man to the inevitably result of "loading of value" in a certain imitation system.